226k views
1 vote
-3(-x+4)=5+3(x+1) please help​

User Byron
by
4.9k points

2 Answers

4 votes

Answer:

no solutions

Explanation:

distribute the parenthesis

3x - 12 = 5 + 3x + 3

move all variables to one side of the equation and the constants to the other

3x - 3x = 5 + 3 + 12

0 = 20

there are no solutions

User Thomas Verbeek
by
4.2k points
4 votes

Answer:

No solution.

Explanation:

Step 1: Write equation

-3(-x + 4) = 5 + 3(x + 1)

Step 2: Solve for x

  1. Distribute: 3x - 12 = 5 + 3x + 3
  2. Combine like terms: 3x - 12 = 3x + 8
  3. Subtract 3x on both sides: -12 ≠ 8

Here, we see that x has to equal no solution. No value of x would make the equation true.

User Dagalpin
by
5.0k points